2003
DOI: 10.1002/jbm.b.10023
|View full text |Cite
|
Sign up to set email alerts
|

Frontal sinus and skull bone defect obliteration with three synthetic bioactive materials. A comparative study

Abstract: Three synthetic bioactive materials were studied in an experimental model to compare their usability in a frontal sinus and a skull bone defect obliteration. Bioactive glass number 9 (BAG(1)), bioactive glass number 13 (BAG(2)), and hydroxyapatite (HA) granules were investigated. BAG(1) and HA granules have been previously tested clinically. The clinical usefulness of BAG(2) granules has not been tested. Upper bony walls of 45 Elco rabbits' frontal sinuses were drilled open from four separate holes with the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
0
43
0
1
Order By: Relevance
“…As the healing process progressed, connective tissue was seen between the BAG granules and, furthermore, fibrous tissue was replaced by lamellar new bone formation, which was seen as a slight increase of HU in ROI analysis. In experimental studies, BAG produces more new bone than hydroxyapatite, [32][33][34] and the bone produced by BAG is very similar to natural frontal bone. 32 In this clinical study, the FTIR studies showed bone produced by BAG to be very similar to natural human frontal bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the healing process progressed, connective tissue was seen between the BAG granules and, furthermore, fibrous tissue was replaced by lamellar new bone formation, which was seen as a slight increase of HU in ROI analysis. In experimental studies, BAG produces more new bone than hydroxyapatite, [32][33][34] and the bone produced by BAG is very similar to natural frontal bone. 32 In this clinical study, the FTIR studies showed bone produced by BAG to be very similar to natural human frontal bone.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, BAG produces more new bone than hydroxyapatite, [32][33][34] and the bone produced by BAG is very similar to natural frontal bone. 32 In this clinical study, the FTIR studies showed bone produced by BAG to be very similar to natural human frontal bone. The properties of BAG are important factors in obliteration material, that is, in chronic infected frontal sinuses, with a relative risk of reinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used without reconstruction of the anterior table with bone or titanium mesh they may lead to long-term defects of contour. 1,17,19,22,23,[26][27][28][29]34,36 Autologous fat and cancellous bone are frequently used to obliterate the frontal sinus when treating frontal sinus fractures. Successful obliteration requires meticulous extirpation of the sinus mucosa and obliteration of the drainage system.…”
Section: Discussionmentioning
confidence: 99%
“…Those materials have presented varying degrees of success for frontal sinus obliteration. [27][28][29][30][31][32][33][34][35][36][37][38] This article reviews patients who sustained frontal sinus fractures treated by obliteration of the sinus with autogenous cancellous bone.…”
mentioning
confidence: 99%